PENERAPAN TEKNOLOGI FERMENTASI PADA BIOPROSES FERMENTASI MINYAK KELAPA (FERMIKEL) [Bioprocessing of Fermented Coconut Oil by Application of Fermentation Technology] - Sulistyo, Joko; Soeka, Yati Sudaryati; Triana, Evi; Napitupulu, Rostiati NR; Joko Sulistyo (BERITA BIOLOGI, 1999)
Methods of extracting oil from coconut endosperm by fermentatbn were studied. The factors which must be controlled to break the emulsion and liberate oil were investigated. It was found that grinding conditions exerted a profound effect upon the stability of the coconut milk emulsion. The optimum condition for rapid fermentathn of coconut milk was related to the condition during incubation period. The fermentation progressed best under mild conditions (28°C-40°Cj. The fermentation was successful in breaking the emulsion at a relatively broad of range and titrable acidity. Coconut cream and small volume of coconut water and "lontar" (palmyra palmj-sap were incubated separately with some strains of Bacillus species, which were preincubated in a coconut tomato-extract sugar (CTSj medium using a shaker, and grown as a starter under conditions that allowed for coconut oil production at pH 4,0-5,0 and 30 C°- 40 "C for 12-24 h. The organism destabilizes the emulsion, apparently by metabolizing sugars, resulting in the production of protein curd and high-quality oil. The palm sap and coconut water to the cream ratio of fermentation medium influenced the performance of oil produced and the bacteria grew well and produced oil in non sterile systems. The oil recovered was about 25 to 20% while average amount of oil in the coconut is approximately 25-35%, which means that only 83,33 to 66,67% oil was recovered. The oil contained little free fatty acid and very low concentration of cholesterol (0,0095 mg/ml), while the traditional coconut oil and commercially palm oil were 0,0111 mg/ml and 0,0132 mg/ml, respectively.